PARTNER VIOLENCE AND WOMEN’S HEALTH REPORTED TO THE FAMILY COMMISSARIES IN CALI, COLOMBIA - Canaval, Gladys E; González, Martha Cecilia; Humphreys, Janice; De Leóne, Nileth; González, Shirley (Investigación y Educación en Enfermería, 2009)
<!– [if gte mso 9]> <![endif]–><!– [if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]–><!– [if gte mso 9]> <![endif]–><!– [if gte mso 10]> <![endif]–> Objective: to measure the effect of partner’ s violence on women’s mental health asking help to the Family Commissaries of Cali, Colombia. Methodology: cross-sectional design with a sample of women that denounce their situation to the Family Commissaries of Cali. The Check List of Symptom -SCL-90R, the Conflict Resolution Tactics and the Resilience scales are applied. Results: the sample comprises 100 women. The Global Distress Index is 1.36; the Distress Index for Positive Symptom is 2.27; nine dimensions of symptoms obtain high scores. Comparison with normative samples of psychiatric out-patients do not show statistical significant differences for most of the indexes; 60% of women present post-traumatic stress disorder. Discussion: the findings are similar to normative samples from psychiatric out – patients. The partner’s violence effect on mental health is considerable and calls for action. Women have needs related with care. They need help to gain or develop personal skills and external resources to handle partner’s violence.